Effects of Kevlar® 29 yarn twist on tensile and tribological properties of self-lubricating fabric liner - Ma, J.; Fan, B.; Gao, Y.; Gu, D.; Qi, X.; Dong, Yu; Hu, Z.; Yang, Y.; Zhang, Q.; Zhao, Y. (SAGE Publications, 2016)
Yarn twist in textile technology is an important characteristic since it considerably affects the properties of knitted or woven fabrics. Many researchers have investigated the effect of staple-spun yarn twist on the properties of the yarns and fabrics. However, the effects of twist level of Kevlar® 29 filament yarn on the properties of yarn and its resin-impregnated self-lubricating fabric liner are not fully known yet. In this study, we have investigated the effects of Kevlar® 29 twist level on the tensile and tribological properties of the fabric liner (Kevlar® 29/polytetrafluoroethylene fabric-resin composite). Two unexpected findings about the effect of yarn twist have been observed, namely (1) asynchronous twist effect on the yarn’s and the liner’s tensile strength and (2) dissimilar yarn twist effect on the liner’s performance. These findings are mainly attributed to the synergic contributions of the yarn twist and strength and the interaction of the resin with the yarn orientation in the woven fabric structure of the liner.